Effect of preoperative oral carbohydrate loading versus oral rehydration solution on enhanced recovery after surgery in elective open gynecological surgeries: A prospective interventional study - Saniya Jaiswal; Pooja Singh; Vaishali Waindeskar; Sunaina Tejpal Karna; K. Pushpalatha; Pranita Mandal (Journal of Anaesthesiology Clinical Pharmacology)
Background and Aims: Enhanced recovery after surgery recommends preoperative consumption of carbohydrate within 2 hours before elective surgery to reduce perioperative discomfort and improve patient outcome. Material and Methods: This prospective interventional study included 105 adult patients, undergoing elective open gynecological surgery under neuraxial anesthesia. Groups I, II, and III were administered commercially available preoperative carbohydrate drink, oral rehydration solution (ORS), and mineral water, respectively, at night and 3 hours before surgery. The primary objective was to assess the difference in hunger, thirst, anxiety, nausea, and fatigue using visual analog scale, postoperative blood sugar levels, and quality of recovery (QoR) 40 questionnaire among groups. Results: Severe hunger (22.9%), thirst (31.4%), and anxiety (34.3%) were experienced more in group III, while in group I and II, no patient had severe discomfort. The mean blood sugar levels in group III (111.3 ± 12.3, 129.4 ± 7.3) were higher compared to group I and II at both 1 hour and 24 hours after initiation of anesthesia. The mean QoR score was the highest in group I compared to group II and group III (P < 0.001). The majority of the patients in group I (77.1%) had an early return of gastrointestinal function and a shorter length of hospital stay. Conclusions: The overall effectiveness of commercially available preoperative carbohydrate solution was more compared to ORS and mineral water. The consumption of ORS drink resulted in less thirst and satisfactory outcomes due to its higher electrolyte content, making it a suitable option for low resource setting.